Digital histogram-based damage assessment of e-glass reinforced concrete cylinders - Sahat Maruli Sihombing; Ibnu Hajar; Roy Lamrun Sianturi; Supriadi; Achmad Jusuf Zulfikar (JTTM : Jurnal Terapan Teknik Mesin, 2026)
Concrete cylinders are extensively utilized as standardized specimens to evaluate the mechanical behavior of structural concrete; however, their inherently low tensile strength makes them highly vulnerable to crack initiation and brittle fracture under splitting tensile loading. Although external confinement using E-glass fiber reinforced polymer (GFRP) laminates has been widely reported to enhance tensile performance, the quantitative relationship between mechanical improvement and surface crack evolution remains insufficiently established. Accordingly, this study aims to: (1) evaluate the splitting tensile strength (STS) of concrete cylinders confined with varying numbers of E-glass laminate layers; (2) quantify surface damage using a digital histogram-based crack area percentage (PCA) method; and (3) analyze the correlation between tensile strength enhancement and crack propagation characteristics. The experimental program was conducted at the Materials and Structural Testing Laboratory, Universitas Medan Area, using cylindrical specimens wrapped with one to four E-glass layers and tested under ASTM C496 splitting tensile procedures. The results demonstrate a progressive increase in STS from 2.48 MPa (control) to 3.88 MPa (four layers), representing a 56.5% improvement, with ANOVA confirming statistical significance (p = 0.003). Digital histogram analysis revealed an increase in PCA from 3.12% to 8.19%, with a strong positive correlation (r = 0.87) between STS and crack distribution. These findings indicate that enhanced confinement promotes distributed cracking and improved energy dissipation rather than brittle localization, thereby establishing a comprehensive mechanical–digital damage assessment framework for FRP-confined concrete systems.